Selenium Modulates Oxidative Stress‐Induced TRPM2 Cation Channel Currents in Transfected Chinese Hamster Ovary Cells. (5th October 2012) - Nazıroğlu, Mustafa; Özgül, Cemil; Küçükayaz, Mustafa; Çiğ, Bilal; Hebeisen, Simon; Bal, Ramazan
Abstract It has been recently reported that the essential antioxidant element selenium has protective effects on cytosolic Ca2+ levels in cell lines. However, the effects of selenium on like transient receptor potential melastatin 2 (TRPM2) in response to oxidative stress (H2O2) are not well understood. We investigated the effects of selenium on H2O2‐induced TRPM2 channel currents in the Chinese hamster ovary (CHO) cell line using patch‐clamp and fura‐2 fluorescence imaging techniques.